Pembuktian Ketegaklurusan Garis terhadap Bidang pada Kubus dan Balok Abstrak - Fitri, Yuliani; Yudhi, Prima (JOSTECH: Journal of Science and Technology, 2021)
Geometry is a compulsory course conducted in mathematics department at university level. In mathematics syllabus, geometry is divided into two dimensional and three dimensional figures. Two dimensional geometry focuses on points, lines, dimension, and angle. Meanwhile, three dimensional geometry focuses on three dimensional figures consisting of some two dimensional figures such as cubes, beams, prisms, pyramids, extra. In this article, geometry aspects are focused on line perpendicularity to dimension in cubes and beams because connectivity between line perpendicularity and dimension is, generally, found on cubes and beams. Hopefully, by proving theorem of line perpendicularity, it can be useful in understanding the characteristics of cubes and beams.